International Outsourcing and the Productivity of Low-skilled Labour in the EU - Hartmut Egger; Peter Egger (Austrian Institute of Economic Research (WIFO), 2001)
This paper presents first insights into the role of international outsourcing on the productivity of low-skilled workers in EU manufacturing. Whereas in the short run international outsourcing exhibits a negative marginal effect on real value added per low-skilled worker, the long-run parameter estimates reveal a positive impact. This may be explained by imperfections on European labor and goods markets, which prohibit an instant adjustment in the factor employment and the output structure. The change in the outsourcing intensity since 1993 alone acounts for a long-run increase of about 3.3% in the real value added per low-skilled worker.
Keywords: C33; F14; F15; 330; International outsourcing; Productivity effects; Panel Econometrics; Internationale Arbeitsteilung; Outsourcing; Ungelernte Arbeitskräfte; Arbeitsproduktivität; Industrie; Schätzung; EU-Staaten